Synthesis and Evaluation of Antimicrobial Activity of Some 1,5(6)-H/or -Methyl-2-subtituted Benzimidazole Derivatives - ALGUL, OZTEKIN; DURAN, NIZAMI; GULBOL, GULAY (Asian Journal of Chemistry, 2010)
In this study, the investigation of structure-activitiy relationships for some newly synthesized benzimidazole structures was aimed. For this purpose, eight compounds having 1,5(6)-H/or-CH3 and 2-substituted benzimidazole structures were synthesized. Subsequently, their antimicrobial activities were examined. These compounds were tested in vitro against three Gram positive (Enterococcus faecalis, Staphylocccus aureus and Staphylocccus epidermidis) and two Gram negative bacteria (Escherichia coli, Pseudomonas aeruginosa). In addition, they were screened in vitro for their antifungal activities. All of these compounds inhibited the growth of Gram positive and Gram negative bacteria at MIC values between 12.5 and 200 μg/mL and had MIC values between 50 and 200 μg/mL for the following fungi (Candida albicans, Candida krusei, Candida glabrata, Candida tropicalis and Candida parapsilosis).